European warm-season temperature and hydroclimate since 850 CE - Mary Gagen (Environmental Research Letters, 2019)
The long-term relationship between temperature and rainfall variables (hydroclimate) remains uncertain due to the short length of instrumental measurements and inconsistent results from climate model simulations. This lack of understanding is critical with regard to projecting future drought and flood risks. Here we assess northern Hemisphere summertime co-variability patterns between temperature and rainfall, over Europe back to 850 CE using instrumental measurements, tree-ring reconstructions, and climate model simulations. We find the temperature–hydroclimate relationship, in both the instrumental and proxt data to be more positive at lower frequencies, but less so in model simulations. In comp[arison to instrumental climate data, climate model simulations reveal a more negative co-variability between temperature and hydroclimate, across all timescales both lower and higher frequency. The reconstructions exhibit more positive co-variability. Despite observed differences in the temperature–hydroclimate co-variability patterns in instrumental, reconstructed and model simulated data, all data types share similar phase-relationships between temperature and hydroclimate, all of which indicate the common influence of external forcing of the climate system. The co-variability between temperature and soil moisture in the model simulations is overestimated, implying a possible overestimation of temperature-driven future drought risks.